4‐Phosphonated or 4‐Free 1, 2, 3‐Triazoles: What Controls the Dimroth Reaction of Arylazides with 2‐Oxopropylphosphonates?. Issue 1 (2nd January 2020) - Pokhodylo, Nazariy T.; Shyyka, Olga Ya.; Goreshnik, Evgeny A.; Obushak, Mykola D.
Abstract: The influence of base‐solvent systems and substituents on the reaction of aryl azides with dimethyl 2‐oxopropylphosphonate was studied. It was shown that azides with electron‐withdrawing substituents in K2 CO3 /DMSO medium (mild conditions) afford 5‐methyl‐1‐aryl‐1 H ‐1, 2, 3‐triazole‐4‐ylphosphonates as major products. In contrast, azides with electron‐donating substituents produce 1‐aryl‐5‐methyl‐1 H ‐1, 2, 3‐triazoles. Based on the obtained results the plausible mechanisms of the reactions were discussed and key points of selectivity control were indicated. Abstract : The reaction of aryl azides with dimethyl 2‐oxopropylphosphonate was studied. The 5‐methyl‐1‐aryl‐1 H ‐1, 2, 3‐triazole‐4‐ylphosphonates were major products when azides with electron‐withdrawing substituents in K2 CO3 /DMSO medium (mild conditions) were used. The plausible mechanisms of the reactions were discussed and key points of selectivity control were indicated.